Do business graduates' attributes fulfill industry requirements and expectations? - Daud S.; Sapuan N.M.; Abidin N.; Rajadurai J. (2023)
Employers complain that graduates from Higher Education Institutions do not meet their expectations in today's volatile economic environment and urge them to produce employable graduates who are able to compete and contribute to the current market. This study examines the perceived gap between important dimensions of graduate attributes and the actual performance of these graduates once employed. The study was carried out in two phases, namely Phase 1 which involved a focus group session and Phase 2 which focused on establishing a questionnaire appropriate for the study across a diverse range of industries. The questionnaires were distributed to managers selected from a list provided by the Higher Education Institution Alumni Centre. Graduates' attributes were analyzed in terms of their knowledge, skills, abilities and personality. The results of this study indicate that managers attach different weightings to different aspects of the graduates' performance and that the Higher Education Institution should target the improvement of soft skills and the development of specific personality components such as openness and extroversion personalities when developing their curriculum. The study highlights the practicality of importance-performance analysis as a means of assessing and directing ongoing human capital development efforts within the higher education sector. The use of importance-performance analysis to evaluate the managers' perceptions of graduates can identify how graduates are performing and specific problem areas and facilitate improvement in curriculum design for their Higher Education Institution.